BEHAVIORISTIC PARADIGM IN EARLY CHILDREN'S EDUCATION: DON'T KNOW THEN DON'T LOVE - Firmina Nai (Academic Journal of Educational Sciences, 2021)
Mardigu Wowiek (2021) one of YouTubers the very famous in providing insight on various issues of political, economic, and political Indonesia, even the economic strategies of America and China today, said that small children can still be shaped by parents at home and teachers in schools. Good parents and teachers teach, not teach! Better parents and teachers set an example, not tell! The best parents and teachers are inspiring! These three things are done through self-talk because: Speech determines action! Action determines habit! Habit determines mindset! Mindset determines self talk! To change yourself to be a good parent and teacher for early childhood, is to change self-talk, as Michael Jackson said..”If you the word, you must start with the man in the mirror”